Dielectric nanofluids for transformers: a review on stability, dielectric, thermophysical, and chemical properties - A. Farade, Rizwan; Abdul Wahab, Noor Izzri; A. Mansour, Diaa Eldin; Rafiq, Muhammad; Yunus Khan, T. M.; Shaik, Abdul Saddique; Zdanowski, Maciej; Ganachari, Sharanabasava V.; Kumar Rajamony, Reji; Ahamad Khatik, Ramjan; Nazeer, Abdul (Institute of Electrical and Electronics Engineers, 2025)
Dielectric nanofluids are an advanced form of transformer liquid insulators with better performance as compared to traditional dielectric fluids. This review systematically examines the existing literature on stability of dielectric nanofluids, including influencing factors, stabilization methods, and long-term stability, as well as nanoparticle-enhanced insulating fluids in terms of dielectric, thermophysical, and chemical properties. This review shows that dielectric nanofluids have multifaceted advantages if size, agglomeration, and zeta potential can be controlled for improved stability, through surface functionalization, ultrasonication, and surfactants. However, aging effects necessitate periodic stability checks for industrial applications. Moreover, nanofluids offer improved dielectric properties (higher AC/Lightning impulse (LI) -breakdown voltage, higher partial discharge inception voltage (PDIV), streamers propagation inhibited, lower dissipation factor (tan δ)); enhanced thermal performance (higher thermal conductivity and heat dissipation); favourable physicochemical properties (moderate viscosity rise controllable through surfactants/nanoparticle reduced loading and higher flash/fire points than base fluids, the low pour points maintained, and chemical benefits (lower acidity, slower degradation of cellulose and higher flash points). While mineral oil based nanofluids exhibit the best performance. A standardized nanoparticle dispersion protocol and validation of stability over time in realistic operational scenarios is paramount for industrial uptake. As shown through experimental evidence, nanofluids have been shown to outperform the ordinary insulating oils in many parameters, with an average enhancement of approximately 21% in AC breakdown voltage. The review also provides an overview of challenges and directions for future research. Such improvements make nanofluids a candidate for the next generation of reliable, high-efficiency transformers.